2018
DOI: 10.3390/jcdd5020021
|View full text |Cite
|
Sign up to set email alerts
|

Enlightening the Association between Bicuspid Aortic Valve and Aortopathy

Abstract: Bicuspid aortic valve (BAV) patients have an increased incidence of developing aortic dilation. Despite its importance, the pathogenesis of aortopathy in BAV is still largely undetermined. Nowadays, intense focus falls both on BAV morphology and progression of valvular dysfunction and on the development of aortic dilation. However, less is known about the relationship between aortic valve morphology and aortic dilation. A better understanding of the molecular pathways involved in the homeostasis of the aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 192 publications
(246 reference statements)
1
15
0
1
Order By: Relevance
“…Matrix metalloproteases (MMP) are also differentially expressed across different aortic sites in BAV, with higher levels of MMP-2 and tissue inhibitor of metalloprotease (TIMP)-3 observed in the concavity of the ascending aorta (29). When comparing convex and concave portions of dilated aortas of BAV patients, similar trends are noted in microRNA expression of these proteins (21,30). These findings strongly support the hypothesis that bicuspid aortopathy is influenced by active cellular processes.…”
Section: B Aortic Tissue Characteristics and Mechanismsupporting
confidence: 55%
See 3 more Smart Citations
“…Matrix metalloproteases (MMP) are also differentially expressed across different aortic sites in BAV, with higher levels of MMP-2 and tissue inhibitor of metalloprotease (TIMP)-3 observed in the concavity of the ascending aorta (29). When comparing convex and concave portions of dilated aortas of BAV patients, similar trends are noted in microRNA expression of these proteins (21,30). These findings strongly support the hypothesis that bicuspid aortopathy is influenced by active cellular processes.…”
Section: B Aortic Tissue Characteristics and Mechanismsupporting
confidence: 55%
“…However, the fiber architecture is similar to that of the normal aorta (24). It has been shown that bicuspid aortopathy shares similarities with Marfan aortopathy: BAV aortic tissues have lower fibrillin content and greater TGF-β1 levels which is due to the disease (21,25,26).…”
Section: B Aortic Tissue Characteristics and Mechanismmentioning
confidence: 96%
See 2 more Smart Citations
“…Focusing on hemodynamic causes, the bicuspid morphology of the aortic valve causes an abnormal biochemical environment, a consequence mainly of the non-physiological hemodynamic impact on the ascending aorta. This morphology-associated helical flow alteration that propagates flow eccentricity leads to increased wall shear stress on the endothelium and progressive dilation of the ascending aorta [18,19]. Although BAV disease is asymptomatic initially, the lack of an early diagnosis can lead to identifying the case in advanced stages or after an event.…”
Section: Discussionmentioning
confidence: 99%